Determination of Naval Based Locations: Strategy to Maximize Performance Monitoring of Defense and Security System in The Sea (Study on Maritime Security and Defense System in Indonesia) - Ahmadi -; Djumilah Zain; Soerachman -; Budi Santoso (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
The Location determination is a strategic issue both in business and public. There are many factors leads to management decisions in expanding or relocating their business facilities. A few existing theory and method in determining location have tend to refer to the profit oriented issues, where more of its decision variables are able to measured precisely. The most common method used was procedure ranks method, gravitational centre analysis method and the linear programming method. Recent development have shown that many location determination issues have been resolve by using Analytical Hierarchy Process (AHP) method. A few disadvantage of the traditional AHP method that was requirement of every factors or indicators in the same level to be independent have been anticipated by using Fuzzy sets theory approach. The military base location determination is a complex issue which involve unmeasurable variables. Fuzzy AHP method which was developed from a very good traditional AHP methodology used to solve multi-criteria decision making that involves variables that can not be measured accurately, such as problems of determining the location of military bases. This study uses six factors/variables with 27 indicators into consideration in the decision making process to determine where the Naval base right. Data processing results show that respondents from all stakeholders in general tend to put the weight of the defense factor, security factor and the factor of ideology as a factor that has the greatest weight to be taken into consideration. The final result of the determination of alternative locations, placing the eastern of Indonesia as an alternative with the highest priority. western of Indonesian is the second priority, the last alternative is western of Indonesia.Keywords: Location determination, military base, AHP Fuzzy